A holobiont view of island biogeography: Unravelling patterns driving the nascent diversification of a Hawaiian spider and its microbial associates. Issue 4 (15th December 2021) - Armstrong, Ellie E.; Perez‐Lamarque, Benoît; Bi, Ke; Chen, Cerise; Becking, Leontine E.; Lim, Jun Ying; Linderoth, Tyler; Krehenwinkel, Henrik; Gillespie, Rosemary G.
Abstract: The diversification of a host lineage can be influenced by both the external environment and its assemblage of microbes. Here, we use a young lineage of spiders, distributed along a chronologically arranged series of volcanic mountains, to investigate how their associated microbial communities have changed as the spiders colonized new locations. Using the stick spider Ariamnes waikula (Araneae, Theridiidae) on the island of Hawaiʻi, and outgroup taxa on older islands, we tested whether each component of the "holobiont" (spider hosts, intracellular endosymbionts and gut microbial communities) showed correlated signatures of diversity due to sequential colonization from older to younger volcanoes. To investigate this, we generated ddRAD data for the host spiders and 16S rRNA gene amplicon data from their microbiota. We expected sequential colonizations to result in a (phylo)genetic structuring of the host spiders and in a diversity gradient in microbial communities. The results showed that the host A . waikula is indeed structured by geographical isolation, suggesting sequential colonization from older to younger volcanoes. Similarly, the endosymbiont communities were markedly different between Ariamnes species on different islands, but more homogeneous among A . waikula populations on the island of Hawaiʻi. Conversely, the gut microbiota, which we suspect is generally environmentally derived, was largely conserved across all populations and species. Our results show that different components of the holobiont respond in distinct ways to the dynamic environment of the volcanic archipelago. This highlights the necessity of understanding the interplay between different components of the holobiont, to properly characterize its evolution.